Analyzing Factors related to Parents’ Self Efficacy with Children’s Cancer Treatment - Ikeu Nurhidayah; Henny Suzana Mediani; Laili Rahayuwati (Journal of Nursing Care, 2019)
The incidence of childhood cancer in Indonesia increased annually. The successful treatment of childhood cancer remains low. One of the factors that influence cancer care was parent’s self-efficacy. Adequate parent’s self-efficacy would improve the quality of care in children with cancer, however, limited studies examine factors associated with parent’s self-efficacy. The aim of this study was to identify factors associated with parent’s self-efficacy in order to undergo cancer treatment. The type of research was descriptive analytic. The population was parents with cancer children. This study was conducted in childhood cancer shelter home community, 40 parents were chosen using the consecutive sampling technique. Self-efficacy was measured using a questionnaire. Data were analyzed with univariate and bivariate analysis. The results showed that 23 (57.5%) of parents have higher self-efficacy. There were significant relationship between enactive mastery experience (p =0.011), vicarious experience (p=0.030), verbal persuasion (p=0.003), the nature of the task faced (p=0.022), external incentives (p=0,009), the status or role of the individual in the environment (p=0.024) and education level (p=0.031) with parent’s self-efficacy. While the physiological state (p=0.284), parent’s sex (p=0.277), parent’s age (p=0.513), and parent’s culture (p=0.174) were not significantly associated with parental self-efficacy in the treatment of childhood cancer. Based on these results, it was very clear that parents who have higher self-efficacy are expected to carry out their duties better, so nurses should provide opportunities and support for families to demonstrate the capabilities and competence of the family to meet the care needs for child cancer.